Further discussion on the separation of linear and nonlinear components in HRTEM imaging. (June 2021) - Chen, Mukun; Ge, Binghui
Highlights: The separation of linear and nonlinear component in HRTEM imaging is studied with possible experimental parameters included. Robustness of the method is verified. Margin of error of image shift is 4 pixels (about 0.13 nm) with AlN as an example; As to the defocus value, is about 2 nm and the spherical aberration, about 6 μm; In the case of high-fold aberrations, such as A2 and B2, 100 nm and 40 nm. Abstract: A method for separating linear and nonlinear components in high-resolution transmission electron microscope imaging has been reported by Chang (Microscopy, 2016. 65: p. 465–472), and a deep understanding has been obtained as to the variation of the linear and nonlinear components with the sample thickness. However, the images used for the separation in the abovementioned study are simulated under ideal conditions, without considering errors in experiments. Therefore, in this study, to verify the practicability of the abovementioned method, experimental details will be systematically considered, such as image mismatch, inaccuracy of the spherical aberration, focus, and residual highfold aberrations A 2, B 2 etc., based on the AlN simulated image, to determine the margin of error of the abovementioned parameters and provide theoretical guidance for experiments.